Development and Validation of patient information leaflet for HIV/AIDS patients - E, Vigneshwaran; RY, Padmanabha; N, Devanna (Indian Journal of Pharmacy Practice)
HIV/AIDS is a chronic disease and the patients are frequently prescribed with multiple long term therapy where it requires educating the patients regarding their disease and about the drugs for an effective management. Previous studies established that leaflets are a cheap and potential way to convey health information, but there is another concern is that how successfully it is ensuring quality information towards target community. This study was undertaken to develop and ensure quality information of one of the supplementary reading material, known as patient information leaflet (PIL) for educating HIV/AIDS patients. Patient information leaflet was prepared in two parts for disease and drug aspects of HIV/AIDS and tested for validity by using EQIP(ensuring quality information for patients) method. PMOSE/IKIRSCH readability scale was used for the estimation of readability and complexity of patient information leaflets. It was concluded that the leaflet for HIV/AIDS can be used as a source of patient information and can be circulated among HIV/AIDS patients to provide patient education and counseling, but it should be reviewed within one to two years.
Keywords: PIL; HIV/AIDS; Ensuring quality information for patients; readability